1995
DOI: 10.1083/jcb.129.5.1391
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the retina cell surface N-acetylgalactosaminylphosphotransferase with an endogenous proteoglycan ligand results in inhibition of cadherin-mediated adhesion.

Abstract: Abstract.We have previously shown that the binding to cells of a monoclonal antibody directed against the chick neural retina N-acetylgalactosaminylphosphotransferase (GalNAcPTase) results in inhibition of cadherin-mediated adhesion and neurite outgrowth. We hypothesized that the antibody mimics the action of an endogenous ligand. Chondroitin sulfate proteoglycans (CSPGs) are potential ligands because they inhibit adhesion and neurite outgrowth and are present in situ at barriers to neuronal growth. We therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 60 publications
2
61
0
2
Order By: Relevance
“…While ␤-catenin associates with vascular endothelialcadherin in newly formed and loosely adherent EC junctions, ␥-catenin predominates in tightly confluent EC-EC junctions (Lampugnani et al, 1997). Tyrosine phosphorylation of ZA protein components reduces intercellular EC-EC adhesion (Esser et al, 1998) and disrupts the linkage between cadherin and the actin cytoskeleton (Balsamo et al, 1995;Hazan and Norton, 1998). Tyrosine phosphorylation of ␥-catenin, ␤-catenin, and p120 Cas induced by ligand occupancy of the epidermal growth factor receptor diminishes cell-cell adhesion through disruption of the cadherin-actin cytoskeletal linkage (Hazan and Norton, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While ␤-catenin associates with vascular endothelialcadherin in newly formed and loosely adherent EC junctions, ␥-catenin predominates in tightly confluent EC-EC junctions (Lampugnani et al, 1997). Tyrosine phosphorylation of ZA protein components reduces intercellular EC-EC adhesion (Esser et al, 1998) and disrupts the linkage between cadherin and the actin cytoskeleton (Balsamo et al, 1995;Hazan and Norton, 1998). Tyrosine phosphorylation of ␥-catenin, ␤-catenin, and p120 Cas induced by ligand occupancy of the epidermal growth factor receptor diminishes cell-cell adhesion through disruption of the cadherin-actin cytoskeletal linkage (Hazan and Norton, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Upon p120 ctn knockdown with siRNA (small interfering RNA), the cadherins are rapidly degraded, probably via ubiquitination (Davis et al, 2003). Also, proteases like MMP (Paradies and Grunwald, 1993), caspase-3 (Hunter et al, 2001) and presenilin (Marambaud et al, 2003) Balsamo et al, 1991Balsamo et al, 1995Guo et al, 2003 Abbreviations used: GATA-4, zinc finger transcription factor recognizes the consensus motif (A/T)GATA(A/G); SOX9, DNA binding SRY box found in SOX family member; Pax6, paired box protein 6; HOXD3, Homeobox D3; HGF, hepatocyte growth factor; EGF, epidermal growth factor; IL-6, interleukin 6; siRNA, small interfering RNA; TF, transcription factor; PKC, protein kinase C; CBP, CREB binding protein; CREB, cyclic AMP response element binding protein.…”
Section: N-cadherin Up-and Downregulationmentioning
confidence: 99%
“…This observation of non-neural tissue localization of neurocan in meninges, skin, and mesenchyme could point to neural crest cells, transient cell populations which form the meninges, the melanocytes which give rise to the pigment of the skin and hair, and supply mesenchyme to several other developing organs. Neurocan has also been reported to be expressed in the heart and vasculature of avian embryos [7,8], and in mouse T lymphocytes [9] and neoplastic mammary glands [10].…”
Section: Discussionmentioning
confidence: 99%
“…The neurocan function is elusive [4][5][6][7][8]25]. In vitro studies have shown that neurocan is able to modulate cell-binding, axon guidance and synapse formation during the development of the nervous system via adhesion molecules [3,11,13,27].…”
mentioning
confidence: 99%